Interakcije zdravil za zdravljenje revmatičnih bolezni - Roškar, Robert (Farmacevtski vestnik, 2013)
In this article interaction of drugs for treatment of rheumatic diseases are reviewed. For the most of these drugs a vast number of interactions have been described but only a minority with clinical importance. The majority of potentially relevant drug interactions exist for cyclosporine A, followed by methotrexate and non-steroidal anti-inflammatory drugs. Frequent and severe interactions in terms of adverse effects, sometimes with life-threatening consequences, occur in methotrexate and trimethoprim/sulfamethoxazole combination as well as in azathioprine and allopurinol comedication. Biological drugs do not show important interactions with other drugs. Treatment of rheumatic diseases is due to their nature commonly associated with polypharmacy, which increases the risk of drugdrug interactions, especially in elderly population with rheumatic diseases and other chronic illnesses.
Keywords: drug; interakcije; revmatična obolenja; zdravila